2004
DOI: 10.1111/j.1365-313x.2004.02203.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the plasma membrane‐localized NDR1 protein results in enhanced bacterial disease resistance in Arabidopsis thaliana

Abstract: Previous studies have established that mutations in the NDR1 gene in Arabidopsis thaliana suppress the resistance response of three resistance proteins, RPS2, RPM1, and RPS5, to Pseudomonas syringae pv. tomato (Pst) strain DC3000 containing the cognate effector genes, avrRpt2, avrRpm1, and avrpPhB, respectively. NDR1 is a plasma membrane (PM)-localized protein, and undergoes several post-translational modifications including carboxy-terminal processing and N-linked glycosylation. Expression of NDR1 under the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 94 publications
(162 reference statements)
6
140
0
1
Order By: Relevance
“…As shown in Figure 2A, following transient coexpression of both genes for 40 h in N. benthamiana leaves by Agrobacterium infection, we observed that both HA:NDR1 and T7:RIN4 can be shown to associate in a series of coimmunoprecipitation experiments. Moreover, using HA:NDR1 epitope-tagged complemented ndr1-1 mutant Arabidopsis plants (Coppinger et al, 2004), we were successful in demonstrating a specific interaction between RIN4 and NDR1 ( Figure 2B). The in planta coimmunoprecipitation experiment validates our initial yeast two-hybrid results demonstrating that NDR1 and RIN4 physically associate in planta.…”
Section: Ndr1 and Rin4 Interact In Plantamentioning
confidence: 91%
See 3 more Smart Citations
“…As shown in Figure 2A, following transient coexpression of both genes for 40 h in N. benthamiana leaves by Agrobacterium infection, we observed that both HA:NDR1 and T7:RIN4 can be shown to associate in a series of coimmunoprecipitation experiments. Moreover, using HA:NDR1 epitope-tagged complemented ndr1-1 mutant Arabidopsis plants (Coppinger et al, 2004), we were successful in demonstrating a specific interaction between RIN4 and NDR1 ( Figure 2B). The in planta coimmunoprecipitation experiment validates our initial yeast two-hybrid results demonstrating that NDR1 and RIN4 physically associate in planta.…”
Section: Ndr1 and Rin4 Interact In Plantamentioning
confidence: 91%
“…Our working hypothesis is that NDR1 assumes a double anchor membrane conformation: anchored at the N terminus by a transmembrane domain (residues 19 to 34) and at the C terminus by the addition of the GPI anchor (Coppinger et al, 2004). If our working model for NDR1's topology is correct, the 18 N-terminal amino acids of NDR1 are the only residues that lie within the cytoplasm and thus are positioned to interact with the cytoplasmically facing plasma membrane-localized RIN4.…”
Section: The N Terminus Of Ndr1 Is Required For Rin4 Associationmentioning
confidence: 99%
See 2 more Smart Citations
“…NDR1 is a critical player in this pathway, as ndr1-1 sober1-1 double mutants were fully susceptible to Pst DC3000 AvrBsT HYB -HA infection. NDR1 is a plasma membrane glycophosphatidylinositol-anchored protein required for the activation of disease resistance signaling for a number of R proteins in Arabidopsis (Coppinger et al, 2004). Mutations in EDS1, PAD4, SID2, and NPR1 only partially compromised sober1-1 resistance, whereas a JAR1 mutant had no effect.…”
Section: Discussionmentioning
confidence: 99%